2015
DOI: 10.1111/mmi.12954
|View full text |Cite
|
Sign up to set email alerts
|

The Crc protein participates in down‐regulation of the Lon gene to promote rhamnolipid production and rhl quorum sensing in Pseudomonas aeruginosa

Abstract: SummaryRhamnolipid acts as a virulence factor during Pseudomonas aeruginosa infection. Here, we show that deletion of the catabolite repression control (crc) gene in P. aeruginosa leads to a rhamnolipid-negative phenotype. This effect is mediated by the downregulation of rhl quorum sensing (QS). We discover that a disruption of the gene encoding the Lon protease entirely offsets the effect of crc deletion on the production of both rhamnolipid and rhl QS signal C4-HSL. Crc is unable to bind lon mRNA in vitro in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 83 publications
4
77
0
Order By: Relevance
“…However, it appears that some key players in CCR play important roles in the regulation of QS. For instance, the deletion of hfq in P. aeruginosa leads to reduced production of rhl QS signal C4-HSL (Sonnleitner et al 2006;Yang et al 2015). Similar effect was observed for the deletion of crc in P. aeruginosa (Yang et al 2015).…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, it appears that some key players in CCR play important roles in the regulation of QS. For instance, the deletion of hfq in P. aeruginosa leads to reduced production of rhl QS signal C4-HSL (Sonnleitner et al 2006;Yang et al 2015). Similar effect was observed for the deletion of crc in P. aeruginosa (Yang et al 2015).…”
Section: Introductionsupporting
confidence: 73%
“…For instance, the deletion of hfq in P. aeruginosa leads to reduced production of rhl QS signal C4-HSL (Sonnleitner et al 2006;Yang et al 2015). Similar effect was observed for the deletion of crc in P. aeruginosa (Yang et al 2015). In addition, it has been reported that Crc modulates the pqs signaling in P. aeruginosa in a nutrient-dependent manner (Zhang et al 2013).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations